Jackfruit Seed Flour as a Functional Ingredient in Conventional Bread: Impact on Proximate Composition and Overall Acceptability (SAARC Journal of Agriculture, 2026)
Despite their nutritional importance, jackfruit seeds are rarely used in food preparations due to their recalcitrant nature and limited availability after the seasonal glut. The study aimed to create nutritious bread enriched with the jackfruit seed flour in place of wheat flour. The nutritional, physical and sensorial properties of bread using various proportions (0, 5, 10 and 15%) of jackfruit seed flour were examined. The results of proximate analysis revealed that adding 15% jackfruit seed flour to breads significantly (P